Adiponectin: Its role in obesity-associated colon and prostate cancers. (August 2017) - Muppala, Santoshi; Konduru, Siva K.P.; Merchant, Neha; Ramsoondar, Judy; Rampersad, Carlos Karan; Rajitha, Balney; Mukund, Vidya; Kancherla, Jyothsna; Hammond, Anthea; Barik, Tapan Kumar; Mannarapu, Mastan; Alam, Afroz; et al.
Highlights: We review the role of adiponectin in obesity-linked colorectal and prostate cancer. We discuss the physiological and biological functions of adiponectin. We outline the role of adiponectin receptors in both colorectal and prostate cancer. We discuss adiponectin and its receptors as possible novel prognostic factors. Abstract: Adipose tissue synthesizes many proteins and hormones collectively called adipokines, which are linked to a number of diseases, including cancer. Low levels of adiponectin are reported to be a risk factor for obesity-related cancers including colorectal and prostate cancers. Accordingly, obesity/lifestyle-related diseases, including certain cancers, may be treated by developing drugs that act specifically on adiponectin levels in circulation. Adiponectin may also serve as a clinical biomarker in obesity-related diseases. Adiponectin-based therapies are known to inhibit cancer advancement and thus may provide a therapeutic approach to delay cancer progression. Better understanding of the function of adiponectin is of great significance in the fight against cancer. This timely review is concentrated on the role of adiponectin and the impact of obesity on the development of cancers, especially colorectal and prostate cancers.